Distinguishing Between Darts and Arrows in the Archaeological Record: Implications for Technological Change in the American West. Issue 4 (20th October 2012) - Hildebrandt, William R.; King, Jerome H.
Abstract: We propose a new method for differentiating archaeological atlatl darts from arrow points. Our dart-arrow index accurately distinguishes known (hafted) archaeological examples of darts and arrows. We find that ethnographic collections of hafted arrows used by previous researchers are problematic, and should not be used as control samples for differentiating darts from arrows. We use the dart-arrow index to reassess the projectile points described by Ames et al. (2010). The analysis shows that Hatwai Eared (4400–2800 B.P.) and Cascade (8500–4500 B.P.) points were darts, not arrows as Ames et al. argue, and that a major revision of the history of bow-and-arrow technology in western North America is unnecessary.